Developmental and Degenerative Characterization of Porcine Parthenogenetic Fetuses during Early Pregnancy - In-Sul Hwang; Mi-Ryung Park; Hae-Sun Lee; Tae-Uk Kwak; Hwa-Young Son; Jong-Koo Kang; Jeong-Woong Lee; Kichoon Lee; Eung-Woo Park; Seongsoo Hwang (Animals, 2020)
The difference between early pregnancy and delivery rate is quite large in assisted reproduction techniques (ARTs), including animal cloning. However, it is not clear why the implanted fetuses aborted after the early pregnancy stage. In the present study, we tried to evaluate the developmental and morphological characteristics of porcine parthenogenetically activated (PA) embryos or fetuses by electric stimulation during the early pregnancy period. The implanted PA and artificially inseminated (AI) embryos and fetuses were collected at day 26 and 35 after embryo transfer, respectively. The developmental and morphological parameters in the PA embryos at day 26 were similar to the AI embryos. The size, weight, formation of major organs, and apoptotic cells were not statistically different in both embryos at day 26. However, the PA fetuses at day 35 showed ceased fetal development and degenerated with abnormal morphologies in their organs. The day 35 PA fetuses showed significantly higher apoptotic cells and lower methylation status in three differentially methylated regions of the H19 gene compared to their comparators. Therefore, the normal development of PA embryos and fetuses during early gestation could lead to these pregnancies being misinterpreted as normal and become one of the main reasons for the gap between early pregnancy and delivery rate.